Maternal High Fat Diet Affects Offspring’s Vitamin K-Dependent Proteins Expression Levels - Lanham, Stuart (PLoS One, 2015)
Studies suggest bone growth & development and susceptibility to vascular disease in later life are influenced by maternal nutrition, during intrauterine and early postnatal life. There is evidence for a role of vitamin K-dependent proteins (VKDPs) including Osteocalcin, Matrix-gla protein, Periostin, and Gas6, in bone and vascular development. This study extends the analysis of VKDPs previously conducted in 6 week old offspring, into offspring of 30 weeks of age, to assess the longer term effects of a maternal and postnatal high fat (HF) diet on VKDP expression. Overall a HF maternal diet and offspring diet exacerbated the bone changes observed. Sex specific and tissue specific differences were observed in VKDP expression for both aorta and femoral tissues. In addition, significant correlations were observed between femoral OCN, Periostin Gas6, and Vkor expression levels and measures of femoral bone structure. Furthermore, MGP, OCN, Ggcx and Vkor expression levels correlated to mass and fat volume, in both sexes. In summary the current study has highlighted the importance of the long-term effects of maternal nutrition on offspring bone development and the correlation of VKDPs to bone structure.